Efektifitas Penggunaan Silika dari Abu Sekam Padi sebagai Katalis pada Material Penyimpan Hidrogen Sistem MgH2 - Jalil, Zulkarnain; Pajriana, Elisa; Rahwanto, Adi (Jurnal Matematika dan Sains, 2017)
Magnesium (Mg) and its alloys are among the potential candidates as materials for hydrogen stor-age applications because they have the ability to absorb hydrogen in large quantities. However Mg has a drawback, ie kinetic reaction is quite slow. For that we need an intensive effort to overcome this, one of them is with catalyst insertion. In this paper, we report on the use of silica catalyst (SiO2) from rice husk ash in the MgH2 hydrogen storage material. SiO2 material inserted into MgH2 of 1 wt%, 3wt% and 5wt% using high energy ball milling technique. Results of observations by XRD showed a milling process that lasted for 5 hours successfully reduced to nanokristal scale. The emerging phase, from the XRD observation, is the MgH2 phase as the most dominant phase. Thermal characterization with DSC showed that the addition of SiO2 was able to decrease the desorption time and temperature of 338,720C in 14.75 minutes in 5wt% catalyst variation.